2011
DOI: 10.1038/bjc.2011.364
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nomogram to predict progression-free survival in patients with platinum-sensitive recurrent ovarian cancer

Abstract: Background:Patients with platinum-sensitive recurrent ovarian cancer are a heterogeneous group, and it is not possible to accurately predict the progression-free survival (PFS) in these patients. We developed and validated a nomogram to help improve prediction of PFS in patients treated with platinum-based chemotherapy.Methods:The nomogram was developed in a training cohort (n=955) from the CALYPSO trial and validated in the AGO-OVAR 2.5 Study (n=340). The proportional-hazards model (nomogram) was based on pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
1
21
1
4
Order By: Relevance
“…Both subjects demonstrated a PFS2 > PFS1 in response to OCDC vaccination as second-line therapy following relapse from first-line therapy. The comparison of second versus first PFS is important in assessing studies of novel chemotherapy or immunologic treatment strategies for patients with relapsed disease including ovarian cancers, and is used to model second response based on first-response duration (31) and interpret the clinical efficacy of second-line therapies (32). Especially interesting is the durable remission in S3, whom after two recurrences remains to date in remission for a total of 44 months, of which 24 months on no additional therapy since the last vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Both subjects demonstrated a PFS2 > PFS1 in response to OCDC vaccination as second-line therapy following relapse from first-line therapy. The comparison of second versus first PFS is important in assessing studies of novel chemotherapy or immunologic treatment strategies for patients with relapsed disease including ovarian cancers, and is used to model second response based on first-response duration (31) and interpret the clinical efficacy of second-line therapies (32). Especially interesting is the durable remission in S3, whom after two recurrences remains to date in remission for a total of 44 months, of which 24 months on no additional therapy since the last vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Initial response rates to standard primary treatments, including cytoreductive surgery and platinum-based combined chemotherapy, are approximately 80%, but most patients with advanced disease relapse within 2 years [2]. Relapse of epithelial ovarian cancer (EOC) occurs in a heterogeneous group of patients, with a wide variation in progression-free survival ranging from a few weeks to N3 years [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was also demonstrated that there is an association between chemotherapy-induced myelotoxicity and patient outcome in a number of malignancies, including lung, breast, gastric, ovarian and colorectal cancer (30)(31)(32)(33)(34)(35)(36)(37)(38). A meta-analysis of 13 trials on various types of cancers (n=9,528) demonstrated a 31% reduction in the mortality risk for patients with a higher grade of neutropenia or leukopenia, compared to patients with lower-grade or no cytopenia (39).…”
Section: Discussionmentioning
confidence: 99%